Prevalence of COVID-19 in children affected by allergic rhinoconjunctivitis and asthma: results from the second "SIAIP rhinosinusitis and conjunctivitis committee" survey - Giulia Brindisi; Anna Maria Zicari; Giuseppe Fabio Parisi; Lucia Diaferio; Cristiana Indolfi; Giuseppe Marchese; Daniele Giovanni Ghiglioni; Giuseppina Rosaria Umano; Angela Klain; Gian Luigi Marseglia; Michele Miraglia Del Giudice (BMC, 2022)
Abstract Background The role of allergic sensitization seems to be protective against SARS CoV2 infection. The aim of this study was to evaluate, using online surveys, the impact of COVID-19 on Italian allergic children, comparing the prevalence of AR and asthma symptoms between the first and second pandemic wave. Methods Both surveys were emailed to Italian pediatricians in April 2020 (first survey) and in March 2021 (second survey). The first one was related to the impact of COVID-19 and the most frequently reported symptoms. The second one was superimposed on the previous one, taking into account some additional aspects in the management of disease. Results A total of 99 pediatricians participated in the first survey and 267 in the second one. The first survey showed that, asthma and allergic rhinoconjunctivitis prevalence was mostly between 0 and 20% throughout the country. The second survey showed a lower prevalence of both diseases nationwide in comparison to the first one. Comparing the two surveys, statistically significant differences were reported only in the distribution of asthma prevalence in Southern Italy while no differences were highlighted in the North and in the Center. Finally regarding allergic rhinoconjunctivitis prevalence, no differences were noticed nationwide. Conclusions Allergic rhinoconjunctivitis and asthma, if under control, did not represent risk factors for the susceptibility to SARS CoV2. Therefore, it is strongly recommended to continue therapies during COVID-19 outbreak, according to the international guidelines. However, being COVID-19 a new disease, actual knowledge will undergo continuous improvements over time.